THE IMPACT OF COVID-19 PANDEMIC ON VULNERABLE GROUPS IN POST-DISASTER AREA - ferianto, Fiki; Hapsa, Hapsa; Ramadhan, Muzaik (Natapraja, 2023)
The COVID-19 pandemic has caused economic crises in many parts of the world, including post-disaster areas in Indonesia. Various studies have found that COVID-19 has caused most people to lose their livelihoods, leading to more severe poverty. However, not much is known about the impact of COVID-19 on Vulnerable Groups in post-disaster areas. The approach used in this research is descriptive qualitative where data is collected through interviews, observation, and utilizing secondary data. This study found that the pandemic caused worse conditions for vulnerable groups in post-disaster areas. The impact can be seen from both social and economic aspects. Socially, the pandemic has changed the livelihood patterns of vulnerable groups, ranging from changes in the type and number of business products to changing professions from farmers to construction workers. In addition, female family heads and the elderly are often stigmatized during the pandemic. Violence against children has also increased significantly. Economically, the pandemic has led to an increase in the unemployment in the disaster area. Female heads of household have experienced shrinking incomes and have contributed to the poverty rate. Businesses in the affected areas have difficulty accessing capital due to lack of business legality from the government.